2008
DOI: 10.1002/14651858.cd000011.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for enhancing medication adherence

Abstract: BackgroundPeople who are prescribed self-administered medications typically take less than half the prescribed doses. Efforts to assist patients with adherence to medications might improve the benefits of prescribed medications, but also might increase their adverse effects. ObjectivesTo update a review summarizing the results of randomized controlled trials (RCTs) of interventions to help patients follow prescriptions for medications for medical problems, including mental disorders but not addictions. Search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
550
1
26

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 802 publications
(618 citation statements)
references
References 363 publications
17
550
1
26
Order By: Relevance
“…MI is effective as a pretreatment adjunct and as an approach for less motivated or prepared patients, and may be applied for a wide range of medications across diverse populations. 11,44 Another communication technique that promotes patientcenteredness and helps guide medication-related discussions is a theory-based counseling model called the 5 A's. This model has been shown to be suitable for application in busy healthcare environments and does not require sophisticated skills or experience.…”
Section: Motivational Interviewing and Counselingmentioning
confidence: 99%
See 1 more Smart Citation
“…MI is effective as a pretreatment adjunct and as an approach for less motivated or prepared patients, and may be applied for a wide range of medications across diverse populations. 11,44 Another communication technique that promotes patientcenteredness and helps guide medication-related discussions is a theory-based counseling model called the 5 A's. This model has been shown to be suitable for application in busy healthcare environments and does not require sophisticated skills or experience.…”
Section: Motivational Interviewing and Counselingmentioning
confidence: 99%
“…Several evidence reviews have identified interventions with modest effects in promoting both overall and condition-specific medication adherence. [11][12][13][14][15][16] Given the complex, multifactorial cause of medication non-adherence, interventions can be similarly multifactorial and multi-level. In this paper we focus on the physician-patient level to furnish providers with a guide to applying adherence research in the clinical encounter.…”
mentioning
confidence: 99%
“…A recent systematic review of interventions to improve adherence to medicines prescribed for long-term treatments found that, while behaviour can be changed, effects were often small and short-lived. 9 The limited success of interventions has been attributed to deficits in both their development and design. 10 Interventions often have not been developed based on a theoretical model of adherence.…”
Section: Improving Adherencementioning
confidence: 99%
“…However, the literature has been dominated by small-scale feasibility and exploratory studies and pilot evaluations that lack statistical power [26,29]. For patients with asthma, digital support services may provide a highly accessible and effective means of monitoring and improving adherence to treatment and disease control.…”
Section: Introductionmentioning
confidence: 99%